Chronic Cannabis indica exposure and neurodegenerative vulnerability: a review of observational evidence - Dhang, Saikat; Chakraborty, Ayeshik (International Journal of Research in Medical Sciences, 2026)
Neurodegenerative diseases are marked by the gradual loss of neurons due to factors such as protein toxicity, oxidative stress, and inflammation, resulting in declining cognitive and motor abilities. Alzheimer’s disease (AD), Parkinson’s disease (PD), and related dementias contribute significantly to global morbidity and mortality. Identifying modifiable risk factors is essential. This retrospective review synthesises available clinical and observational evidence exploring the association between chronic Cannabis indica exposure and neurodegenerative outcomes. A retrospective review of published observational studies and clinical records was conducted. Data sources included neurology and psychiatry case records and peer-reviewed literature reporting chronic Cannabis indica use and neurodegenerative outcomes. Primary outcomes were cognitive impairment, dementia syndromes, Parkinsonian features, and neuroimaging evidence of neurodegeneration. Chronic cannabis use was consistently associated with structural and functional brain alterations, particularly in CB1-rich regions such as the medial temporal cortex, orbitofrontal cortex, insula, and hippocampus. Neuroimaging studies reported reduced gray matter volume and altered white matter integrity, with functional connectivity changes. Evidence also suggests chronic exposure disrupts glutamatergic and GABAergic signaling and contributes to cognitive deficits in learning, executive function, memory, and attention. In dementia and Parkinson’s cohorts, cannabis abuse was linked with increased emergency visits and higher pain burden. Observational evidence indicates a potential neurodegenerative vulnerability associated with chronic Cannabis indica use. Prospective longitudinal studies with standardized exposure metrics are required to clarify causality and inform public health policy.